Development of Novel Continuous and Interval Exercise Programs by Applying the FITT-VP Principle in Dogs - H. S. Lee; S. H. Lee; J. W. Kim; Y. S. Lee; B. C. Lee; H. J. Oh; J. H. Kim (The Scientific World Journal)
Although proper exercise training induces positive physiological effects, improper exercise can lead to injury, fatigue, and poor performance. The frequency, intensity, time/duration, type, volume, and progression (FITT-VP) are the essential components of exercise training to maintain or improve physical fitness and health. The purpose of this study was to develop specific exercise programs by applying the FITT-VP principle and to examine the effects on heart rate (HR) and hematological and biochemical parameters in dogs. The healthy male Beagles (n = 4) included in this study performed continuous and interval exercises, comprising 12 protocols. The HR monitoring elicited an affirmative response to activities but varied depending on the protocols. The hematologic parameters (e.g., red blood cell count, white blood cell count, hemoglobin, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration) were within the reference ranges both before and after exercise. The creatine kinase level significantly increased, and the cholesterol level decreased after exercises. In conclusion, the continuous and interval exercise program elicits an appropriate HR reaction, has no adverse effects on the serum parameters, and provides valuable insight for healthcare in dogs.